2021
DOI: 10.1186/s12909-021-02959-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of peer assisted learning in online clinical skills training of ophthalmology module

Abstract: Background Online communication has taken over in the last 2 years due to the frequent lockdowns because of the COVID-19 pandemic. Overburdened physicians in this pandemic are struggling to get enough time to teach clinical skills online to the students. Also, due to student’s safety issues, the students cannot fully attend the clinics. Therefore, in this scenario, online PAL (Peer Assisted Learning) sessions for clinical skill teaching and learning can be an effective alternative for undergrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The study's results showed that most PreCOVID and COVID students attended an average of 6 to 10 simulation sessions. This finding is similar to other studies conducted worldwide (Alabdulwahhab et al, 2021;Nisar et al, 2021;Thomas et al, 2020). In this study, more students in the COVID group participated in simulation sessions than in the PreCOVID group.…”
Section: Text Mining Of Open-ended Questionssupporting
confidence: 92%
See 1 more Smart Citation
“…The study's results showed that most PreCOVID and COVID students attended an average of 6 to 10 simulation sessions. This finding is similar to other studies conducted worldwide (Alabdulwahhab et al, 2021;Nisar et al, 2021;Thomas et al, 2020). In this study, more students in the COVID group participated in simulation sessions than in the PreCOVID group.…”
Section: Text Mining Of Open-ended Questionssupporting
confidence: 92%
“…It allows trainees to learn from their failures in a controlled environment, helping them to avoid making the same mistakes in the real world (Wang et al, 2021). Studies have shown that SBME is an 3 of 17 effective learning method for medical students, with age and gender distributions comparable to previous research (Nisar et al, 2021;Wang et al, 2021). The primary goal of these studies was to determine the effectiveness of SBME as a learning pedagogy for medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the chaos caused by the pandemic, there always have been beneficial lessons learned, and these should always be remembered. Globally, many specific medical courses have been reported to be affected by COVID, e.g., obstetrics and gynecology [34], neurosurgery [35], orthopedics [36], ophthalmology [37], Anatomy [38], and of course there are many others publication that we have not had the chance to explore in detail via the internet. however, to the best of our knowledge, this is the first publication on the impact of COVID on Microbiology exam result for medical students.…”
Section: Resultsmentioning
confidence: 99%
“…Teaching methods in this section should be fun, engaging, and pedagogically sound to establish an open environment for communication. Problem‐based learning (PBL)/case‐based learning (CBL) flip‐classrooms can be transitioned online, while peer‐assisted learning and group learning are implemented during preparation for discussions 8–11 . This section improves the students' enthusiasm for studying and encourages them to study actively and creatively to achieve higher learning goals.…”
Section: Concepts and Methodsmentioning
confidence: 99%
“…Problem-based learning (PBL)/case-based learning (CBL) flip-classrooms can be transitioned online, while peer-assisted learning and group learning are implemented during preparation for discussions. [8][9][10][11] This section improves the students' enthusiasm for studying and encourages them to study actively and creatively to achieve higher learning goals. A mixed assessment composed of peer and teacher assessments was applied to evaluate students' performance after the completion of the real-time interactive section for each chapter, which contributed 30% of the final grade.…”
Section: Real-time Interactionmentioning
confidence: 99%